Islamic Financial Literacy and Personal Financial Planning: A Socio-Demographic Study - Arum Setyowati; Harmadi Harmadi; Sunarjanto Sunarjanto (University of Merdeka Malang, 2018)
This study aims to measure the level of Islamic Financial Literacy (IFL) in Solo society and to test the effect of IFL on personal financial planning. The socio-demographic variables such as age, gender, marital status, education level, and income are being used as the control variable. 313 respondents are involved in this research directly through survey method and Ordinary Least Square (OLS) is used to analyze the obtained research data. The study uses purposive sampling method and limiting the education level and income of research respondents. Study questionnaire consists of 20 multiple choice questions to measure respondent IFL and 13 questions to measure respondent personal financial planning. The results showed that: (1) the level of IFL in Solo reach 64.66 percent; (2) people with a good level of IFL tends to have better management in their personal finances; and (3) people with a good level of IFL tends to prefer investing on Islamic asset. Last, this paper will contribute to the scientific development of behavioral finance and financial inclusion which had been highly discussed in the financial literature. This study also became an early research in examining the influence of IFL on personal financial planning.JEL Classification: G2, G4, J1DOI: https://doi.org/10.26905/jkdp.v22i1.1625